2020
DOI: 10.1007/s11696-020-01077-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, antimicrobial activity, and cytotoxic activity of Mikania micrantha Kunth flower essential oil from North East India

Abstract: Mikania micrantha Kunth (mile-a-minute) is a major invasive weed with medicinal properties. It causes destruction of forests and threat to crop plantations, thus affecting the agriculture-based economy of a country. As an attempt to mitigate this problem, we have studied the applicability of M. micrantha flower essential oil against disease causing microorganisms and inhibition of cancerous cells. Sixty-six compounds were characterized from the flower essential oil by gas chromatography-mass spectrometry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Among these, Mikania cordata has been used in traditional herbal medicine for a long to treat various ailments including cancer by folklore people (Uy et al, 2015). Several reporters have also shown the cytotoxic activity of Mikania species (Saikia et al, 2020;Ahammed et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, Mikania cordata has been used in traditional herbal medicine for a long to treat various ailments including cancer by folklore people (Uy et al, 2015). Several reporters have also shown the cytotoxic activity of Mikania species (Saikia et al, 2020;Ahammed et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we reported comparative phenolic contents and antioxidant activity (Khatun et al, 2020), Corresponding author: Md Aziz Abdur Rahman, E-mail: aziz2002@asia.com DOI: https://doi.org/10.3329/bpj.v24i1.51630 antimicrobial activity (Khatun et al, 2017a), and anti-inflammatory and thrombolytic activity (Khatun et al, 2017b) of these three species. A number of published research showed cytotoxic activity of various Mikania species including Mikania cordata (Ali et al, 2011), Mikania micrantha (Saikia et al, 2020) and Mikania scandens (Ahammed et al, 2020). However, comparative cytotoxicity evaluation of these species was not reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported the antiproliferative activity of different medicinal plant in V. radiata model (Charchafchi et al, 2007;Fawzia et al, 2007;Ray et al, 2013;Chetry and Bahrali, 2018). It was also reported that the essential oil extracted from the invasive weed M. micrantha flower has been found to have antimicrobial and anticancer properties (Saikia et al, 2020). The plant M. mirantha was also reported to possess anti-tumour activity (Dou et al, 2014).…”
Section: Effects On Seed Germination and Root Lengthmentioning
confidence: 99%
“…In continuation of our search for bioactive natural constituents from the plants of North East region of Indo-Burma biodiversity herein, [15][16][17] our aim is to investigate the chemical constituents of the essential oil acquired from E communis leaves and subsequently evaluate its antimicrobial, cytotoxic, antioxidant and ACE inhibiting properties.…”
Section: Introductionmentioning
confidence: 99%